РОЛЬ МИСТЕЦЬКИХ ДИСЦИПЛІН У ФАХОВІЙ ПІДГОТОВЦІ ДИЗАЙНЕРІВ (Педагогіка вищої та середньої школи, 2009)
In given article the role of such art disciplines as the academic drawing, the academic painting, a composition in the course of a professional knowledge formation of the future designers in the system of higher educational institutions is defined.